The association between organizational culture and the use of management initiatives in the public sector. (11th April 2017) - Baird, Kevin M.; Harrison, Graeme L.
Abstract: This paper examines the association between five factors in O'Reilly et al. (1991) Organizational Culture Profile and the use of Activity Management (AM), Total Quality Management (TQM) and Employee Empowerment within public sector organizations. The results show that the use of AM and TQM is lower in public sector organizations than in their private sector counterparts, and is facilitated by an organizational culture of Outcome Orientation and Attention to Detail. The extent of use of Employee Empowerment is similar across the two sectors, and is facilitated when public sector organizations exhibit higher Respect for People and Innovation.